Recycling scrap tungsten carbide roll collars. (3rd September 2015) - Liao, Y.-T.; Wu, T.-C.; Chou, T.-C.
Abstract : Tungsten is difficult and costly to maintain, so steel mills are constantly developing recycling technologies for tungsten carbide roll collars, which comprise 85% tungsten, in order to reduce tungsten consumption. However, some key technological barriers have not yet been overcome. This article aims to propose a successful recycling technology breakthrough. Crushed crystallites of scrap tungsten carbide roll collars are mixed with swarf, dropped into a centrifuge and then processed by electroslag remelting. After heat treatment refinement, recycled tungsten alloy roll collars containing only 20% tungsten are made. This experiment demonstrates that tungsten carbide roll collars made by powder metallurgy can be reused after being scrapped to make recycled tungsten alloy roll collars by melting. The trial production data for the recycled tungsten alloy roll collars provide strong evidence that their wear performance and cost savings are better than ordinary alloy collars and that they effectively reduce consumption of tungsten.